The EFFECTIVENESS OF ANESTHESIA MAXHINE DEMONSTRATION IN IMPROVING PRE-ANESTHETIC PREPARATION SKILLS AMONG ANESTHESIOLOGY NURSING STUDENTS - Ahmad fauzan; Niken Anggraini Sri Saputri; Muhaji Muhaji (Journal of Indonesian Anesthesiology Nursing, 2026)
Background: Pre-anesthetic preparation skills are essential for Anesthesiology Nursing students in ensuring patient safety. The demonstration method is considered effective because it provides direct practical experience. Methods: This study employed a quantitative approach with a quasi-experimental pretest–posttest control group design. A total of 76 students were selected using simple random sampling. Data were collected using an observation checklist based on standard operating procedures (SOPs). Data analysis was conducted using the Wilcoxon test and Mann-Whitney test. Results: All respondents were categorized as not competent before the intervention. After the demonstration, there was a significant improvement in skills among the experimental group. The Wilcoxon test showed a Sig. (2-tailed) value of 0.000, and the Mann-Whitney test revealed a p-value of 0.000, indicating a significant difference between the experimental and control groups. Conclusion: Anesthesia machine demonstration was effective in improving pre- anesthetic preparation skills among Anesthesiology Nursing students at Universitas ‘Aisyiyah Yogyakarta, with 81.6% of respondents in the experimental group achieving the fairly competent and competent categories.